Kebutuhan Bahan Ajar Menulis Teks Prosedur Berbasis Discovery Learning - Herlisya, Destia; Anggraini, Tri Riya; Awalludin, Awalludin; Wati, Tri Kurnia (LPPM STKIP PGRI Bandar Lampung, 2024)
The lack of use of e-LKPD in learning procedural texts at the junior high school level is a problem in this study. Therefore, this study aims to analyze the need for developing e-LKPD to write procedural texts based on discovery learning. The method used is descriptive and qualitative with the subject of research being teachers at Al-Kausar Junior High School, Bandar Lampung. The data collection tools used are interview guidelines and documentation. Data analysis uses Miles & Huberman data analysis with data reduction, data presentation, and data validation. The results of the study require schools to use e-LKPD that are in accordance with the curriculum and learning objectives. This study is expected to be a reference in making or developing e-LKPD as a learning medium for writing procedural texts based on discovery learning at the junior high school level.